Caenorhabditis elegans provides an efficient drug screening platform for GNAO1-related disorders and highlights the potential role of caffeine in controlling dyskinesia. Issue 6 (8th October 2021) - Di Rocco, Martina; Galosi, Serena; Lanza, Enrico; Tosato, Federica; Caprini, Davide; Folli, Viola; Friedman, Jennifer; Bocchinfuso, Gianfranco; Martire, Alberto; Di Schiavi, Elia; Leuzzi, Vincenzo; Martinelli, Simone
Abstract: Dominant GNAO1 mutations cause an emerging group of childhood-onset neurological disorders characterized by developmental delay, intellectual disability, movement disorders, drug-resistant seizures and neurological deterioration. GNAO1 encodes the α-subunit of an inhibitory GTP/GDP-binding protein regulating ion channel activity and neurotransmitter release. The pathogenic mechanisms underlying GNAO1 -related disorders remain largely elusive and there are no effective therapies. Here, we assessed the functional impact of two disease-causing variants associated with distinct clinical features, c.139A > G (p.S47G) and c.662C > A (p.A221D), using Caenorhabditis elegans as a model organism. The c.139A > G change was introduced into the orthologous position of the C. elegans gene via CRISPR/Cas9, whereas a knock-in strain carrying the p.A221D variant was already available. Like null mutants, homozygous knock-in animals showed increased egg laying and were hypersensitive to aldicarb, an inhibitor of acetylcholinesterase, suggesting excessive neurotransmitter release by different classes of motor neurons. Automated analysis of C. elegans locomotion indicated that goa-1 mutants move faster than control animals, with more frequent body bends and a higher reversal rate and display uncoordinated locomotion. Phenotypic profiling of heterozygous animals revealed a strong hypomorphic effect of both variants, with a partial dominant-negative activity for the p.A221D allele. Finally, caffeine was shown to rescue aberrant motor function in C. elegans harboring the goa-1 variants; this effect is mainly exerted through adenosine receptor antagonism. Overall, our findings establish a suitable platform for drug discovery, which may assist in accelerating the development of new therapies for this devastating condition, and highlight the potential role of caffeine in controlling GNAO1 -related dyskinesia.